Evaluating clinical pharmacists’ involvement in postoperative acute pain services: a multicenter survey in Guangdong Province, China - Lu, Junxiong; Chen, Mingzhen; He, Guansheng; Chen, Binwei; Wang, Ruolun (Frontiers in Pharmacology, 2023)
Objective: Postoperative acute pain services in China are in their initial stages. This survey aimed to investigate the attitudes, involvement, and knowledge of clinical pharmacists in China regarding postoperative acute pain services. The results can provide valuable information to guide clinical pharmacists in developing targeted strategies to improve their postoperative acute pain service capabilities. Methods: A questionnaire was distributed to the pharmacy departments of 133 grade A tertiary hospitals in Guangdong province, and the responses were collected electronically. Results: 123 completed questionnaires were collected from clinical pharmacists. Although 95.93% of clinical pharmacists believed they should participate in postoperative pain services, only 62.6% reported substantial involvement. Overall satisfaction with the postoperative pain service was 93.5%. Understanding of nonsteroidal anti-inflammatory drugs and opioid analgesics by clinical pharmacists was comparable (p > 0.05). 2 Furthermore, 98.38% of clinical pharmacists desired systematic learning in postoperative pain management, and 40.65% expressed a strong need. Conclusions: Clinical pharmacists in China demonstrate a positive attitude toward participating in postoperative acute pain services. However, the actual level of involvement was concerning, and the lack of systematic training and well-established work protocols may be contributing factors. Efforts should be made to establish comprehensive and standardized processes and work protocols for postoperative acute pain services and provide systematic and hierarchical professional training to enhance clinical pharmacists' capabilities in postoperative acute pain services.